2007
DOI: 10.1007/s11695-007-9103-5
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Bupivicaine Pain Pumps to Eliminate the Need for Patient Controlled Analgesia Pumps in Primary Laparoscopic Roux-en-Y Gastric Bypass

Abstract: The use of a bupivicaine pain pump offers the opportunity to dramatically reduce the use of opioids postoperatively in all bariatric patients by eliminating PCA. This change could potentially reduce the incidence of respiratory failure from oversedation, while offering the same levels of pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…There are numerous recent randomized studies of bariatric patients handled with other strategies proposed to diminish postoperative pain such as bupivacaine pump systems, intraoperative or continuous intraperitoneal bupivacaine application, systemic lidocaine, ultrasound-guided transversus abdominis plane block, etc. [13,[25][26][27][28][29]. These studies render different results, not always reproducible by other authors and expensive to apply in clinical practice in some cases.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are numerous recent randomized studies of bariatric patients handled with other strategies proposed to diminish postoperative pain such as bupivacaine pump systems, intraoperative or continuous intraperitoneal bupivacaine application, systemic lidocaine, ultrasound-guided transversus abdominis plane block, etc. [13,[25][26][27][28][29]. These studies render different results, not always reproducible by other authors and expensive to apply in clinical practice in some cases.…”
Section: Discussionmentioning
confidence: 96%
“…Wound infiltration with local anesthetics proved to be a simple, effective, and inexpensive means of providing good analgesia in laparoscopic cholecystectomy, laparoscopic inguinal hernia repair, and gynecologic laparoscopic surgery [9][10][11][12]. However, few studies have investigated its role in major laparoscopic surgery [13]. To date, no study has investigated the benefits of wound infiltration in the setting of laparoscopic weight loss surgery.…”
mentioning
confidence: 99%
“…Two different studies evaluated intraperitoneal infiltration of bupivacaine with improved pain scores within the first 24 h postoperatively and reduction of postoperative hydrocodone/ acetaminophen requirements compared with the placebo group although study quality was poor and both results lacked clinical relevance [14,15].Postoperative subfascial/subcutaneous infusion of bupivacaine had no effect compared to placebo on pain, opioid use or hospital length stay [16].…”
Section: Local Anesthetics: Intraperitoneally -Subfascially/ Subcutanmentioning
confidence: 99%
“…The pain pumps were not effective in iliac crest bone grafting (22) or radical retropubic prostatectomies (23). Cottam et al (24) showed that there was no difference in postoperative analgesic control after laparoscopic Roux-en-Y gastric bypass surgery between pain pumps and patient-controlled analgesia (PCA). However, there was a significant reduction in opioid use and PONV.…”
Section: Le Point Sur Les Pompes Analgésiques En Chirurgie Esthétiquementioning
confidence: 99%